The Relationship Between the PH Saliva of Pregnant Women who Chewing Betel and the Incidence of Dental Caries - Christina Ngadilah; Leny Marlina A. Pinat; Merniwati Sherly Eluama; Anton Radja Ratu (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Saliva has an important role in detecting several disease and even the method is very easy. People who chewing betel nut, the condition in their mouth will be different from people who do not chewing betel nut. Normal salivary pH is between 6.8-7.2. The aim of this research was to find a relationship between salivary pH in pregnant women who chewing betel nut with the incidence of caries. Methods : A cross sectional studi was conducted to examine the relationship and the study was conducted on 155 pregnant women who chewing betel nut, aged between 16-50 years in remote area and urbanarea Kupang District. The significance value (0.371 > 0.01) between pH and DMF-T (caries) means that there is ni relationship between salivary pH and caries rate. The avarege pH of pregnant women who chewing betel nut 10.13 in the 2nd trimester group and 10.12 in the 3rd trimester group. The avarege caries rate 4.2 for the 2nd trimester group and 4.3 for the 3rd trimester group. Although there is no significant relationship between Salivary pH and caries in pregnant women who chwing betel nut. However, pregnant women who chewing betel nut will cause various kind of damage, both damage to the supporting tissues of the teeth and other systemic damage such as diabetes, heart disease, nephrosis and others. Arecolin and arecaidin in areca nut are carcinogenic and damage the placenta to the mother and baby, resulting in adverse pregnancy outcome.